Pengaruh Harga dan Promosi terhadap Keputusan Pembelian: (Studi Kasus pada Mahasiswa UPG Pengguna Aplikasi Shopee) - Dinal Rahmat Alam; Hismi Hismi; Sahrul Sahrul; Riki Gana Suyatna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to examine the influence of price and promotion on Shopee e-commerce purchasing decisions through a case study of Primagraha University students. Students also often shop through this application by exploring e-commerce. With the prices and promotions offered, many factors influence consumer purchasing decisions. In this research, the author considers price and promotion factors. This research methodology uses quantitative research with Primagraha University student respondents, with 103 respondents who often shop using the Shopee e-commerce application. Then data was obtained using a questionnaire. The results of this research show that the price impact is 8.4% and the promotion impact is 72.8%. Although the combined impact of price and promotion is 60% the remaining 40% is explained by other variables not considered in this study, such as product, location, people, process, physical evidence, wom and others.